Le discours auto-adressé des sujets malades chroniques : un agir sur soi - Lennize Pereira Paulo (Éducation et Socialisation)
This article is a part of a research conducted among a sample of people affected by one or several chronic diseases. This qualitative study tries to identify ways and process used by the subjects affected by chronic disease to design or transform their daily life activities. Based on fourteen qualitative interviews this article postulates that self-directed speech can be considered as a category of instrument (Vygotski) used by the subject to stay alive, bearing in mind that people living with a chronic disease are required to perform specific activities to stay alive and healthy (Tourette-Turgis). Content analysis of interviews shows the existence of different categories of self-directed speech and aims to describe their specificities and functions. The article characterizes different uses of the self-directed speech The author concludes that the use of self-directed speech can be considered as an invariant helping people to handle activities to stay alive and healthy.